Pendidikan Islam Inklusif Berbasis Multikultural Pada Madrasah - Effendi, Hamdan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to find out more about inclusive multicultural-based Islamic education in madrasas. The research method used is descriptive qualitative. Using in-depth interview data collection techniques. The results showed that inclusive education is an educational innovation for people with disabilities. Where they have the same rights as others to live decently with education that facilitates their lives. So this education is a necessity of the world to be realized for all nations. The implementation of inclusion, which has not received a serious response from all levels of society, requires socialization that can provide clarity on the importance of this matter. Although it has not become a serious concern, there have also been several parties who have looked and started implementing it in the community. Inclusion in education is a process of increasing student participation and reducing their separation from the culture, curriculum and local school community. In conclusion, inclusive education comes with a concept that aims to make education accessible to all people, including persons with disabilities, to meet this goal, learning activities should be structured in such a way that adapts the needs, abilities and character of students and refers to the curriculum developed. and supported by the multicultural competence of a teacher. Keywords:, Pnclusive, Multicultural, Islamic Education